Reorganized, weak C–H⋯O interactions directly modify the mechanical properties and compaction performance of a series of nitrobenzoic acids. Issue 18 (25th April 2017) - Singaraju, Aditya B.; Nguyen, Kyle; Swenson, Dale C.; Iyer, Mamta; Haware, Rahul V.; Stevens, Lewis L.
Abstract : Strong hydrogen-bonding interactions are predictably leveraged for local molecular docking; however, weak intermolecular interactions are being increasingly recognized as pivotal governors of extended, supramolecular assembly. Abstract : Strong hydrogen-bonding interactions are predictably leveraged for local molecular docking; however, weak intermolecular interactions are being increasingly recognized as pivotal governors of extended, supramolecular assembly. In this report, a series of nitrobenzoic acids (NBA) – m -nitrobenzoic acid (3-NBA), p -nitrobenzoic acid (4-NBA), 4-methyl-3-NBA (Me-NBA), 4-chloro-3-NBA (Cl-NBA) and 4-bromo-3-NBA (Br-NBA) – are utilized to systematically adjust weak C–H⋯O (nitro) and C–H⋯O (carboxyl) bonding interactions and discriminate their influence on the crystal structure, aggregate elasticity and compaction performance. The expected carboxylic acid dimer persists across the entire NBA series; however, alternative organization of C–H⋯O interactions yields distinct 1-d tapes. The acoustic frequency distributions obtained from powder Brillouin light scattering (BLS) spectra provide supportive interpretation of the strength and anisotropy of the reorganized intermolecular interactions. Aggregate Young's moduli displayed a narrow range from 13.5 GPa for Br-NBA to 9.8 GPa for 3-NBA. However, the maximum longitudinal moduli ( M max ), calculated from the high-frequency cutoff, revealed significant differences in the strength of intermolecular interactions along the 1-d tapes. For 3-NBA, the extended organization of several co-linear C–H⋯O (nitro) interactions yielded an M max of 42.0 GPa, while the remaining NBA materials displayed an M max near 25 GPa. From powder compaction studies, the tabletability rank order was observed as: 3-NBA > 4-NBA > Me-NBA ≈ Br-NBA ≈ Cl-NBA; however, none of the materials achieved a tensile strength greater than 1 MPa. Overall, even minor redistribution of weak intermolecular interactions significantly modifies supramolecular assembly in NBA and detailing the specific contribution of these weak forces is required for substantive structure–performance correlation.